Awareness and Knowledge of Colorectal Cancer Screening Among Medical Students at the University of Aleppo: A Cross-Sectional Study - Zayegh, Obada; Hmidi, Zina Shikh; Nawlo, Ahmad A; Al-Mouakeh, Ahmad; Amin, Basel; Banjah, Bassel; Chammout, Anwar; Alsayid, Muhammad (Avicenna Journal of Medicine, 2022)
Background Colorectal cancer (CRC) is the third leading cause of malignancy in Syria. The aim of our study was to assess the awareness and knowledge of CRC and its screening methods among medical students at the University of Aleppo.Methods A cross-sectional study of medical students at the University of Aleppo was conducted using a self-administered 12-element questionnaire. The questionnaire consisted of demographics, awareness of CRC, knowledge of CRC and its screening methods. Awareness of CRC included three questions asking students if they ever heard of CRC and its screening methods. Knowledge of CRC was evaluated through three sets of questions about CRC risk factors, signs and symptoms, and preventative methods. The students were selected randomly during academic lectures. A χ2 or Fisher's exact tests for categorical variables were used for statistical analysis, as appropriate. A two-sided p < 0.05 was considered statistically significant. We stratified students based on pre-clinical versus clinical years and average academic score.Results A total of 824 students completed the questionnaire. The majority of students were aware of CRC (98.9%) and CRC screening methods (79.8%). Students had poor knowledge of CRC risk factors (16.5% for non-modifiable factors and 11.7% for modifiable factors), signs and symptoms (52.6%), and protective factors (9.9%). Only 31.7% of students were able to identify the appropriate age to initiate screening for average-risk individuals. Clinical students had better awareness and knowledge of CRC and its screening methods. Clinical students with higher academic score showed better awareness and knowledge in some elements.Conclusion Our study reported high awareness and poor knowledge rates of CRC and its screening methods among medical students at the University of Aleppo. Although clinical students had higher awareness and knowledge of CRC compared to pre-clinical students, the impact of academic score revealed variable results.
Keywords: colorectal cancer; screening; Syria; medical students; awareness; knowledge